Effect of TiO2 nanoparticles and multiwall carbon nanotubes on the freshwater diatom Nitzschia frustulum: evaluation of growth, cellular components and morphology. Issue 1 (2nd January 2019) - Jia, Kun; Sun, Chenglong; Wang, Yulin; Li, Xin; Mu, Weijie; Fan, Yawen
ABSTRACT: Great attention should be paid to the possible impacts of various nanoparticles on aquatic organism. Freshwater diatoms are essential components of phytoplankton and play a critical role in bioassessment of nanoparticle exposure in the environment. In this study, cell growth was inhibited by TiO2 -NPs and MWCNTs, the 24 h EC50 values of TiO2 -NPs and MWCNTs to Nitzschia frustulum were 20.75 and 24.64 mg L −1, respectively. Significant decreases of Chl a content after TiO2 -NPs exposures were detected and the Chl a content of N. frustulum was obviously increased by MWCNTs treatment at lower concentration. The ROS was detected in N. frustulum after TiO2 -NPs and MWCNTs exposures. The MDA content was significantly induced by TiO2 -NPs at lower concentrations of 24 and 48 h exposure; meanwhile, it increased at all tested concentrations at 24 h MWCNTs exposure. The SOD enzyme was induced by 72 and 96 h TiO2 -NPs exposure, and increased by MWCNTs treatment at 96 h in N. frustulum . Scanning electron microscopy results revealed that N. frustulum had obvious cell deformation after TiO2 -NPs treatment. The result showed that the physiological and biochemical response mechanisms after NPs exposure of diatom were species-specific, and in relation to the exposure concentration and time.